دراسة تحليلية نقدية لمعايير تقويم الأداء والتعويض من منظور نظرية الوكالة بالتطبيق على المعايير المحاسبية الدولية والمحلية - العربيد, عصام فهد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لقد كان لظهور وقبول نظرية الوكالة تأثيرا" كبيرا" على المحاسبة الإدارية ، والأسئلة المطروحة في هذا الصدد ، هل يمكن استخدام البيانات المحاسبية في عملية تقويم الأداء؟ وهل يمكن استخدام مفاهيم كفاءة أسواق رأس المال كعامل مهم في تحديد قيمة مقاييس الأداء المرتكزة على الأرقام المحاسبية والمستخدمة في تقويم ومكافأة المدراء التنفيذيين؟ والى أي مدى يمكن استخدام خيارات الأسهم لأغراض التحفييز طبقا" للمبادىء المحاسبية المقبولة عموما" بخصوص عقود الخيارات، حيث يوجد علاقة مباشرة بين استخدام خيارات الأسهم والإنتاجية والعائد على الأصول وأسعار الأسهم، حيث يعتبر فشل هيئة المعايير المحاسبية المالية بفرض موضوع التعويض بخيارات الأسهم ، مؤشرا" يطرح عدة تساؤلات حول مدى استمرارية ومصداقية هذه الهيئة. وقد عالج هذا البحث الأوجه المتعددة لمعايير تقويم الأداء من منظور نظرية الوكالة وركز على مشروع المعيار رقم /106/ والخاص بالتعويض على أساس خيارات الأسهم والمعيار الدولي الصادر عن IASB، وتبين أن معايير تقويم الأداء في سورية الصادرة عن وزارة المالية لا تطبق في الواقع العملي والدليل على ذلك معظم مؤسسات القطاع العام الاقتصادية خاسرة لعدم وجود آلية تضع هذا القطاع على ميزان الربح والخسارة وهذا يعني غياب المعايير المالية والمعايير غير المالية. وتوصل الباحث إلى أن هيئة المعايير المحاسبية الدولية تخضع لضغوط كبيرة من اللوبي السياسي والاقتصادي الأمريكي والمدراء التنفيذين في الشركات الكبيرة ولماذا نجحت الهيئة في إصدار العديد من المعايير وفشلت في إصدار المعيار الخاص بالتعويض على أساس خيارات الأسهم. The evolution and acceptance of Agency Theory has had a profound effect on managerial accounting. The question here is that: can we use the accounting data in the performance evaluation process? And can we use the concepts of capital markets as important factors in determining the performance measurement value based on accounting numbers used in evaluation and rewarding the executive directors? And to what extent can we use the stock options for stimulating purposes according to the "General Acceptable Accounting Principles" (GAAP) concerning option contracts, for there is a direct relation between the use of stock and productivity options which is related to estate and stock prices. The failure of the "Financial Accounting Standards Bureau" (FASB) in the stock option compensation issue has raised questions concerning its reliability and survival. This research deals with the different points of performance evaluation standards from the perspective of Agency Theory and concentrates on the project parameter No. 106 that is specific to the compensation on the bases of stock options and the international parameter of IASB. It came to light that performance evaluation standards, issued by the Ministry of Finance, are not applicable in practical life, and the proof is that most public economical institutions suffer losses because of the lack of a mechanism that determines the criteria of loss and gain which means the absence of financial and non-financial standards. The researchers have concluded that the FASB face major pressures from the American economical and political lobbies and from the executive directors of the major companies. They also figured out why the Bureau has succeeded in issuing multiple standards and has failed in issuing the standards of compensation on the bases of stock options.